Contribution to Theoretical Found of the Procedural Witness Protection (Kriminalističke teme, 2008)
This paper attempts to theoretical found the procedural witness protection in conformity with appropriate understanding of common theory of law. Procedural witness protection is perceived as a special legal relation. Author defines its elements (subjective rights and legal obligations) and its assumptions (active and pasive subjects, object, goal and conditions), and illustrates them with numerous examples in comparative law. In this sense is given the definition of witness protection. The main place in that definition belongs to the subjective right to witness protection as a result of the protection of fundamental human rights: right to personal and property safety, right to inviolability of psychic integrity, right to dignity and right to privacy. The fundamental right to witness protection shall include the following rights: right to be notified of the right of protection, right to ask for or to waive the right of protection, right to refuse to give any personal data, statement or to answer the questions until the decision on the request for protection is rendered, right to appeal the decision and right to attorney.The main criterion of their distinction is character of the protection measures. Procedural witness protection counts with the procedural measures. They may be measures of hidden witness identity (personal data and/or appearance and voice) to the common publicity, and exceptionaly to the defense, as also preventing the physical encounter of accused and witness.The latest mentioned measures can be directed to the physical put- ing out of action of intimidation and retaliation, but also to the protecting the spiritual integrity of witness, in other words to the preventing his secondary victimisation. This kind of measures of witness protection can be related to the rules of evidence and to the process coercion. Nonprocedural protection includes the measures of physical-technical witness protection with the police character as part of the program of witness protection.The choice of protection measures is guided by five principles: legality, combination, individualization, proportionality and compensation.